The regulatory agency’s role regarding resolution of disputes in the telecommunication sector: understanding arbitration and mediation through Japanese, British and American experiences - Oliveira, Arthur Coimbra de (Law, State and Telecommunications Review, 2009)
Discussions about the adjudicatory function of the Brazilian telecommunication regulatory agency (ANATEL) are still underrated, in part because the 1997 General Telecommunications Law did not create new and significant tools for the regulator to play that role. This article investigates how foreign regulators tackle disputes between telecommunication companies, focusing on how arbitration and mediation are used for that purpose. It also analyzes ANATEL’s possibilities of acting on such resolution of disputes processes, and proposes how the national regulator might improve this function.